Studies on impact of different levels and frequencies of nitrogen fertigation on capsicum (Capsicum annuum) crop - KANAHIYA, KRISHAN; JHORAR, R K; KUMAR, SANJAY; BUNDELA, D S; KUMAR, MUKESH; MEHLA, MUKESH KUMAR; HARODE, PAVAN KUMAR (The Indian Journal of Agricultural Sciences, 2024)
Capsicum is a major nutrient-rich vegetable crop grown all over India. The drip irrigation method is the best suited for capsicum crop, particularly due to water scarcity. A study was carried out during 2019–20 at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to examine the influence of three different nitrogen fertigation level (75, 100, and 125% RDN) and three different combinations of fertigation frequency i.e. with every irrigation, weekly and fortnightly, with drip irrigation on different parameters of capsicum crop. Urea was applied on the experimental fields as the major source of nitrogen. Fertigation level of 125% RDN applied with every irrigation (FF1FL3) obtained the highest fruit yield (178.4 q/ha), while the lowest yield (158.2 q/ha) was recorded with 75% RDN in FF1FL1 treatment. In comparison to fertigation frequency with every irrigation and 75% RDN, 33.7% and 34.5% more yield was obtained in 100 and 125% RDN treatment. Average plant height, fruit width, fruit length, fruits/plant, and fruit weight were found maximum at 125% RDN, followed by 100% RDN under with every irrigation. The experiment results showed that the highest water use efficiency (3.7 kg/m3) was obtained with treatment FF1FL3, while lowest (3.2 kg/m3) was found in FF3FL1 treatment. However, the treatment with 75% RDN with every irrigation fertigation frequency showed maximum nitrogen use efficiency (134.8). The nitrogen use efficiency increased when the nitrogen fertigation level decreased from 125–75%.